The ‘Other’ physical transformations in 'The Adventures of Tintin' TV series (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Describing a race through the verbal and visual description of physical appearance is often used to create binary opposition between ‘Us’ and ‘Other’, so it does in The Adventures of Tintin comic books by Hergé. In The Adventures of Tintin TV series adaptation (1991-2) by Stéphane Bernasconi, ‘Other’s verbal and visual physical depictions that are portrayed in the comic books undergo transformations that occur on non-White characters. These transformations－changes, additions, and omissions－ can be clearly seen in the Tintin TV series entitled The Blue Lotus, Cigars of the Pharaoh, and The Broken Ear that are adapted from the comic books of the same titles. The theory of adaptation by Linda Hutcheon and Orientalism by Edward Said are used to reveal and explain the adapter’s strategies to make the skin colours, costume, and deformity moderation and negotiation in order that the TV series can be accepted by the audience around the world today.